Selection of Coffee Shop Business Locations Using the Analytical Hierarchy Process Method - Ahmad Fauzi; Novita Indriyani; Andika Bayu Hasta Yanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
The Coffee Shop business is one of the trending businesses in Indonesia, so competition in this business field can be said to be increasing rapidly. In order to get a strategic business location, the majority of decision makers are wrong in choosing the location of their business, this is due to the lack of analysis and to the data from the location survey and the lack of decision-making limitations in analyzing the survey data. For this reason, it is necessary to create a system, where this system uses the Analytical Hierarchy Process (AHP) method to assist in processing survey data. The application of the Analytical Hierarchy Process (AHP) method in determining the location of the Coffee Shop business is determined using 7 (criteria) criteria including rental prices, buildings, clean water, accessibility, distance to offices, internet connections and electricity sources. The final result of the process using the AHP method is ranking of several alternative locations that have been set, and several alternative locations get the highest global weight, it becomes recommendations for the development of this coffee shop business